The self at work: Understanding the experience of community placement in activation schemes in a post-recession context - Petautschnig Arancibia, Carla Pia (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2021)
This thesis aims to explain how long-term unemployed welfare recipients taking part in activation schemes made sense of their experiences of unemployment, job-seeking and placement as they deliberated their past, present and future aspirations sustained by an ongoing tension between contextual and internal change. This study focuses on activation schemes that demand from welfare recipients 19.5 hours per week in a local voluntary and not-for-profit organisation. The thesis used a Constructivist Grounded Theory approach to guide an inductive process of constructing an explicative framework grounded on and in interaction with the data co-constructed by the researcher and research participants. Thirty scheme participants ? whose age ranged between 28 and 64? participated in in-depth interviews across two counties in Ireland. Irish literature on activation reforms, welfare conditionality and the precarisation of the labour market has been increasing; however, little is known about the specific realm of community placement schemes and participants? experiences and aspirations. Hence, this thesis offers an original contribution on the experiences of unemployment and job seeking in a post-recession context that, as the findings showed, meant particular challenges for those closer to retirement age, those with health issues, those skilled in less required positions or with little work experience, and those who have been focused on care responsibilities. The principal contribution of the thesis is a conceptual framework of the experience of placement from the stance of agential reflexivity as participants pondered their possibilities and constraints to project into the future amidst contextual and internal changes. This framework relates to central processes concerning identity, self and future thinking which are shaped by gender and age. Going through long- term unemployment meant changing by losing as participants? disconnection with work as a source of identity, deepened. During this process participants acquired a multifaceted identity, in interaction with institutional demands, that challenged their sense of self: becoming unemployed meant becoming a welfare recipient who was demanded to become an active jobseeker who, despite their efforts, failed to secure a job. Underpinned by the placement period, the process of changing through regaining, made accessible the volunteer-like identity ascribed to the local organisations through which new possibilities appeared to be available and, thus, future thinking re-emerged as participants deliberated courses of action. Men and women expressed different attachment to work as a source of identity, social recognition and future aspirations. While older men longed for the stability of their past working selves, women were oriented towards their future working selves as a project for a renewed identity beyond the realm of care. Largely, participants considered prolonging their time on the scheme or moving on to a second scheme as their first (most realistic / desirable) option.
APPROVED
Keywords: Unemployment; Community placement; Reflexivity; Pathways to Work; Activation